Development Of Nano-Sized Β-Cyclodextrin Polymers As An Adsorbent For The Effective Removal Of Phenolic Compounds From Aqueous Samples - Suwaibatu, Mamman (2021)
The use of cyclodextrin-based materials as adsorbents for removing different contaminants is cutting-edge research that has caught the attention of many researchers worldwide. In this research, magnetite methacrylic acid-functionalized β-cyclodextrin (Fe3O4@MAA-βCD), magnetic molecularly imprinted polymer based on methacrylic acid-functionalized β-cyclodextrin (MMIP MAA-βCD), magnetic non-molecularly imprinted polymer based on methacrylic acid-functionalized β-cyclodextrin (MNIP MAA-βCD, magnetic molecularly imprinted polymer based on methacrylic acid (MMIP MAA) and magnetic non-molecularly imprinted polymer based on methacrylic acid (MNIP MAA) were successfully synthesized for the removal of 2,4- dichlorophenol (2,4-DNP), 2,4-dinitrophenol (2,4-DNP) and bisphenol A (BPA) from aqueous media. The adsorbents were characterized by Fourier transform infrared spectroscopy (FTIR), scanning electron microscope (SEM), transmission electron microscopy (TEM), vibrating sample magnetometer (VSM), Brunauer-Emmett-Teller (BET), thermogravimetric analyzer (TGA) and X-ray Diffraction (XRD). 1H NMR spectroscopy was used to characterize the MAA-βCD and BPA-MAA-βCD inclusion complex. Several variables influencing the adsorption efficiency of the selected phenolic compound have been analyzed in depth. Fe3O4@MAA-βCD gave the optimal removal amount of the studied phenolic compounds studied at pH 2 for 2,4-DNP, pH 7 for 2,4-DCP, and pH 6 for BPA. While the contact time, initial concentration, the adsorbent dose was set at 60 min, 10 mg/L, and 20 mg, respectively.